1977
DOI: 10.1111/j.1348-0421.1977.tb00308.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Development of Membrane Protein of Influenza Virus

Abstract: The intracellular development of membrane protein (MP) of influenza A virus was investigated by immunofluorescent staining. Monospecific antiserum was prepared by immunizing rabbits with MP eluted from SDS-polyacrylamide gels of SDS-disrupted NWS virions. In the productive infection in clone 1-5C-4 cells, MP antigen was first detected over the whole cell at 4 hr after infection, concomitantly with the appearance of hemagglutinin (HA) antigen in the cytoplasm, and bright nuclear fluorescence was then observed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1979
1979
1991
1991

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…It is generally accepted that the NP protein of influenza A virus accumulates in the nucleus (Watson & Coons, 1954;Lui, 1955). Although there is contradictory evidence as to whether the M 1 protein enters the nucleus, several recent reports clearly demonstrated its migration to the nucleus (Maeno et al, 1977;Beesley & Campbell, 1984;Patterson et al, 1988;Bucher et al, 1989), and one such report described nuclear staining of M1 protein which was characterized by more intense staining of the nucleoli, whereas nuclear staining of NP is characterized by the absence of stain from the nucleoli (Bucher et al, 1989). The association of M protein with the nucleoli was observed in HMV-II cells infected with the influenza C/Yamagata/1/88 strain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is generally accepted that the NP protein of influenza A virus accumulates in the nucleus (Watson & Coons, 1954;Lui, 1955). Although there is contradictory evidence as to whether the M 1 protein enters the nucleus, several recent reports clearly demonstrated its migration to the nucleus (Maeno et al, 1977;Beesley & Campbell, 1984;Patterson et al, 1988;Bucher et al, 1989), and one such report described nuclear staining of M1 protein which was characterized by more intense staining of the nucleoli, whereas nuclear staining of NP is characterized by the absence of stain from the nucleoli (Bucher et al, 1989). The association of M protein with the nucleoli was observed in HMV-II cells infected with the influenza C/Yamagata/1/88 strain.…”
Section: Discussionmentioning
confidence: 99%
“…Previous immunofluorescence studies of influenza A virus-infected cells demonstrated that NP accumulated in the nucleus (Watson & Coons, 1954;Lui, 1955;Maeno et al, 1977). The intracellular location of M1 is still controversial, with some reports describing its detection in both the nucleus and the cytoplasm (Gregoriades, 1973;Oxford & Schild, 1975;Hay & Skehel, 1975;Maeno et al, 1977;Patterson et al, 1988;Bucher et al, 1989) whereas others claim that it is absent from the nucleus (Lazarowitz et al, 1971;Krug & Etkind, 1973).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The yield from each undiluted passage was 'used as the inoculum for the succeeding undiluted passage. Hemagglutination (HA), neuraminidase (NA) assay, complement-fixation (CF) test and infectivity titration were described previously (12). Clone 1-5C-4 cells were grown in medium 199 containing 10% fetal calf serum (23).…”
Section: Methodsmentioning
confidence: 99%
“…Densitometer scanning of these polypeptides, showed that the relative amounts of NP polypeptide in the cytoplasm and in the nucleus of standard virus- infected cells were 67% and 33%, and those of 4UP-infected cells were 40% and 60%, respectively. It should be noted here that the band corresponding to NP polypeptide was riot stained for carbohydrate with periodic acid-Schiff reagent (12).…”
Section: Synthesis Of Virus-specific Polypeptidesmentioning
confidence: 99%